Southern sass and killer cravings - Young, Kate (Mystery writer) (Young, Kate (Mystery writer). Marygene Brown., 2019)
For generations, the women of the Brown family on Peach Cove Island have been known for their Southern sass and sweet homemade desserts at their beloved Peach Diner. Since their mother's passing two years ago, Marygene has been stuck in Atlanta while her sister Jena Lynn has been running the family business. Now Marygene has left her husband and returned to her hometown, where she can almost feel Mama's presence. But all is not peachy back home. Marygene has barely tied on an apron when a diner regular drops dead at the counter. When it turns out the old man's been poisoned, Jena Lynn is led away in handcuffs and the family eatery is closed. Now, to save her sister and the diner, Marygene must find the real killer. With some startling assistance from her Mama's spirit, Marygene will be serving up a special order of just desserts . . .